Nutrition among nursing home residents: results from the NutriCare study - Lavriša, Živa; Pravst, Igor; Krušič, Sanja; Hren, Neža; Gregorič, Nadan; Hren, Irena; Koroušić Seljak, Barbara; Hristov, Hristo (Frontiers in Nutrition, 2024)
Background: Older adults living in nursing homes (NH), are considered a vulnerable population in terms of nutrition. The aim of the present study was to explore the usual intake of energy, macronutrients and specific food groups, along with offers in the NH menus on a nationally representative sample of Slovenian nursing home residents and compare dietary patterns with the established recommendations. Methods: The study was conducted as part of a cross-sectional Nutricare study on 317 residents (65-101 years) from 20 Slovenian NH in 9 health regions. Relatively independent residents were selected using quota sampling by sex and age. Data collection involved interviews, anthropometric measurements, and data on usual dietary intake (Multiple source method from two 24h dietary recalls and food frequency questionnaires). Adherence of dietary intake to the recommendations was assessed, as well as dietary composition of NH menus. Mini nutritional assessment was used to explore nutritional status. Results: Notable variability in energy and macronutrient intakes was observed with some participants showing intakes below and others above the recommended values. A high prevalence of BMI > 30 kg/m² was observed in 39% of participants, indicating potential discrepancies between total energy intake and expenditure. The usual intake of fat was 36% of total energy intake (TEI). The intake of foods of animal origin exceeded dietary guidelines. Intake of carbohydrates (46% TEI males, 47% TEI females) as well as dietary fibre (20 g/day both sexes) was below recommendations. A scarce intake of fruits, vegetables and cereals was observed. 40% of males and 35% of females had usual daily protein intakes lower than 1g/kg of body weight. Protein content of breakfast and dinner could be improved. NH residents consumed little food from outside NH. The usual nutrient and food group intakes of residents reflected the NH menu offers. Conclusions: Study results on usual intake of energy, macronutrients, specific food groups, and offers in the NH menus indicate potential for optimisation. According to World Health Organisation, the prevalence of BMI > 30 kg/m² is notable and warrants attention. Careful meal planning and regular monitoring of the nutritional status of NH residents should be considered.